DAYA HAMBAT EKSTRAK DAUN KARI TERHADAP PERTUMBUHAN BAKTERI Staphylococcus aureus - Lisna Unita; Colvin Voon (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2016)
Curry leaves ( Murraya koenigii ) can be used as a spice in cooking and curry leaf extract , has the effect of antimicrobial activity can inhibit the growth of Staphylococcus aureus . The purpose of this study was to determine the curry leaf extract solution of various concentrations to inhibit the growth of Staphylococcus aureus and know the difference inhibition curry leaf extract solution between the various different concentrations on the growth of Staphylococcus aureus . This study uses laboratory Experimental design by Design Posttest only control group design . Test method using agar diffusion techniques and media used are media Mueller Hinton Agar ( MHA ) containing Staphylococcus aureus . After incubation for 24 hours and then measure the inhibition zone which formed . One Way Anova Test results obtained curry leaf extract solutions were made in different concentrations of 2.5 % , 5 % , 7.5 % and 10 % can inhibit the growth of Staphylococcus aureus . The higher concentration of curry leaf extract greater inhibitory power and show stronger antibacterial activity . Multiple Comparison Test Results ( LSD ) significant difference ( p < 0.05 ) between the inhibition of curry leaf extract 2.5 % to 10 % , with a value of p = 0.002 , and curry leaf extract 5 % to 10 % with the value of p = 0.007.